In vitro-antibacterial properties of ten medicinal plants against common uropathogenic organisms and toxicity determination using brine shrimp lethality assay - Jayananda Ilangage Maheshi Kavindya Ilangage; Ilangakoon Arachchige Chethana Sewwandi Ilangakoon; Kariyakarawanage Minoshi Kaushika Fernando; Dissanayaka Mudiyanselage Manisha Kavindu Dissanayake; Nimna Pinimali Deeyagaha Rajapaksha; Lakmini Hasanthika Walpola; Dineshani Hettiarachchi (BMC, 2024)
Abstract Background In recent years, antibiotic resistance has emerged as a global health concern in bacterial infections such as urinary tract infections (UTIs). Uropathogenic Escherichia coli is the most frequent organism responsible for both simple and complex UTIs. Staphylococcus aureus and Pseudomonas aeruginosa are frequently associated with complicated UTIs. Sri Lanka has significant resources of medicinal plants used to cure UTIs in Ayurvedic and traditional medicine. Methods Agar well diffusion and broth microdilution methods were used to determine the antibacterial activity of the methanolic extract of ten medicinal plants against P. aeruginosa ATCC27853, S.aureus ATCC25923, E.coli ATCC25922 and their UTI positive strains extracted from positive culture plates. As a preliminary toxicity assay, the Brine Shrimp Lethality Assay (BSLA) was used to determine its cytotoxicity. Results The methanolic fruits extract of P. emblica demonstrated the highest antibacterial activity against both E. coli ATCC25922 and E. coli UTI-positive strains. B. diffusa roots extract exhibited the highest activity against S. aureus ATCC25923, while T. chebula fruits extract showed the highest activity against the S. aureus UTI-positive strain. T. involucrata roots extract displayed the highest activity against P. aeruginosa ATCC27853, and Z. officinale rhizomes extract showed the highest activity against the P. aeruginosa UTI-positive strain. Moreover, the plant mixture showed the most substantial antibacterial effect against P. aeruginosa ATCC27853. However, the methanolic seed extract of C. melo did not exhibit any antimicrobial effects against the selected organisms. All plant material, including the plant mixture, showed cytotoxicity according to the BSLA. Conclusion All the methanolic extracts including P. emblica fruits, O. tenuiflorum whole plant, T. chebula fruits, Z. officinale rhizome, T. terrestris roots, T. involucrata roots, A. lanata whole plant. B. diffusa roots and A. falcatus roots showed antimicrobial effects against selected strains except C. melo seed extract. The results of the present study evidently supports the traditional and ayurvedic use of these plants for the treatment of UTIs. This paves the way for another praise for new plant-based therapeutic product development for the treatment of UTIs. However, further toxicity studies are needed for medicinal dose determination.